Ruminant Animal Feed From Food Plants In Konawe District, Indonesia - Rina Astarika; Deki Zulkarnain; La Ode Muhammad Munadi; Achmad Selamet Aku; Yamin Yaddi; La Ode Sahaba; Adrian Tawai (Pascasarjana Universitas Sulawesi Tenggara, 2023)
Beef cattle in Indonesia in recent years have continued to decline, which is caused by various factors including slaughter of productive livestock and livestock diseases to feed problems. This research will specifically examine the source of animal feed from food crops in Konawe Regency as an alternative to tackling the fodder shortage originating from forage. This study uses secondary data from the Konawe Regency Statistics Agency 2022 by collecting data from harvested areas of food crops and the population of ruminants such as beef cattle and goats. The data obtained were then processed to facilitate the interpretation of the data and analyzed descriptively using the analysis of the carrying capacity of livestock. The results of the study found that the harvested area of 52.990 hectares of food crops with dry matter production of 100,631.650 kg was able to provide a source of feed for livestock as much as 30,633.68 ST beef cattle and 42,968.25 ST goats.